2010
DOI: 10.1007/s00220-010-1075-y
|View full text |Cite
|
Sign up to set email alerts
|

The Pentagram Map: A Discrete Integrable System

Abstract: The pentagram map is a projectively natural transformation defined on (twisted) polygons. A twisted polygon is a map from Z into RP 2 that is periodic modulo a projective transformation called the monodromy. We find a Poisson structure on the space of twisted polygons and show that the pentagram map relative to this Poisson structure is completely integrable. For certain families of twisted polygons, such as those we call universally convex, we translate the integrability into a statement about the quasi-perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
246
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(266 citation statements)
references
References 26 publications
3
246
0
8
Order By: Relevance
“…, v n ) is mapped to a point which is the intersection of two diagonals (v i−1 , v i+1 ) and (v i , v i+2 ). If n and k + 1 are co-prime, then, as shown in [13], the moduli space of n-gons in RP k is isomorphic, as algebraic varieties, to the space E k+1,n of n-periodic linear difference equations (1.1) V i = a V i+n = (−1) k V i .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, v n ) is mapped to a point which is the intersection of two diagonals (v i−1 , v i+1 ) and (v i , v i+2 ). If n and k + 1 are co-prime, then, as shown in [13], the moduli space of n-gons in RP k is isomorphic, as algebraic varieties, to the space E k+1,n of n-periodic linear difference equations (1.1) V i = a V i+n = (−1) k V i .…”
Section: Introductionmentioning
confidence: 99%
“…In [13] it was shown that the pentagram map is a discrete complete integrable system, i.e. that the space of n-periodic lower-triangular operators (1.1) of order 3 is a Poisson manifold and a complete set of integrals in involution for the pentagram map was constructed.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, in the literature, the above bracket (2.25) is written as 26) where ∇f (X) := χ −1 (df (X)) is the gradient of f at X, i.e.,…”
Section: Lie-poisson Bracket On Gmentioning
confidence: 99%
“…Since T is invariant under projective transformations the map T can be extended to the projective plane on a wider class of generic n-gons called twisted n-gons on RP 2 . In [26] was proved that the pentagram map T is a discrete integrable system in the sense of Liouville-Arnold and it is a discretization of Boussinesq equation.…”
Section: Pentagram Mapmentioning
confidence: 99%
See 1 more Smart Citation